ASESMEN PEMBELAJARAN PROFETIK DALAM PENDIDIKAN ISLAM: STRATEGI HOLISTIK UNTUK PENGUATAN NILAI SPIRITUAL DAN KARAKTER PESERTA DIDIK - Asrofi, Asrofi; Hamilaturroyya, Hamilaturroyya; Purwoko, Purwoko (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Prophetic learning assessment is an innovative approach in Islamic education that integrates spiritual, moral, social, and emotional dimensions in addition to the cognitive aspects of students. This approach is relevant to the implementation of the Pancasila Student Profile because its six dimensions reflect prophetic values ??that are in line with the goals of Islamic education. However, its implementation still faces various challenges such as minimal teacher understanding, lack of structural support, and limited instruments and cultural resistance, so this study aims to formulate a conceptual foundation and relevant strategic solutions. This article examines the basic concepts, principles, methods, and challenges of implementing prophetic assessment through a systematic literature review. The study results indicate that prophetic assessment can be implemented through portfolios, behavioral observations, reflective interviews, and social projects based on humanitarian values. This study is a literature study that collects and analyzes data from various sources such as books and scientific journals to explore the concept and implementation of prophetic learning assessment. The literature used is selectively selected from the latest publications through academic databases, focusing on journal articles and relevant national sources from Google Scholar. However, its implementation faces obstacles such as the limited competence of teachers and the lack of valid assessment instruments.Resistance from the social environment, which still prioritizes academic achievements, also poses a challenge.Therefore, this article recommends strategies such as periodic teacher training, the development of value-based instruments, and collaboration between schools, families, and communities.With structured implementation, prophetic assessment can shape a generation that is intellectually smart, morally resilient, socially sensitive, and deeply spiritual. ABSTRAK Asesmen pembelajaran profetik merupakan pendekatan inovatif dalam pendidikan Islam yang mengintegrasikan dimensi spiritual, moral, sosial, dan emosional selain aspek kognitif peserta didik. Pendekatan ini relevan dengan implementasi Profil Pelajar Pancasila karena keenam dimensinya mencerminkan nilai-nilai profetik yang sejalan dengan tujuan pendidikan Islam. Namun, pelaksanaannya masih menghadapi berbagai tantangan seperti minimnya pemahaman guru, kurangnya dukungan struktural, serta keterbatasan instrumen dan resistensi budaya, sehingga kajian ini bertujuan merumuskan fondasi konseptual dan solusi strategis yang relevan. Artikel ini mengkaji konsep dasar, prinsip, metode, serta tantangan implementasi asesmen profetik melalui kajian literatur sistematis. Hasil kajian menunjukkan bahwa asesmen profetik dapat diterapkan melalui portofolio, observasi perilaku, wawancara reflektif, dan proyek sosial berbasis nilai-nilai kemanusiaan. Penelitian ini merupakan studi kepustakaan yang mengumpulkan dan menganalisis data dari berbagai sumber seperti buku dan jurnal ilmiah untuk mendalami konsep dan implementasi asesmen pembelajaran profetik. Namun, pelaksanaannya menghadapi hambatan seperti keterbatasan kompetensi guru dan kurangnya instrumen penilaian yang valid. Resistensi dari lingkungan sosial yang masih mengutamakan capaian akademik juga menjadi kendala. Untuk itu, artikel ini merekomendasikan strategi seperti pelatihan guru periodik, pengembangan instrumen berbasis nilai, dan kolaborasi antara sekolah, keluarga, dan masyarakat. Dengan penerapan terstruktur, asesmen profetik dapat membentuk generasi yang cerdas intelektual, tangguh moral, peka sosial, dan mendalam spiritualitasnya.